EFFICACY OF POST-STROKE REHABILITATION IN PATIENTS - Davlatova , Muqaddas (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Stroke remains one of the leading causes of disability worldwide. Post-stroke rehabilitation significantly improves motor, sensory, cognitive, and emotional functions, enhances independence in activities of daily living, reduces secondary complications, and positively influences long-term prognosis. The effectiveness of rehabilitation is highest when initiated early (within the first weeks-months), delivered intensively, through a multidisciplinary team approach, and tailored to individual patient characteristics. Modern technologies such as robotic therapy, virtual reality, and telerehabilitation provide additional benefits, particularly in motor recovery and motivation maintenance. Even in the chronic phase, continued rehabilitation helps preserve functional gains and prevents deterioration. Comprehensive, evidence-based rehabilitation not only improves quality of life but also reduces socioeconomic burden associated with post-stroke disability.